Application of the specific education curriculum in the Arabic textbook school - Rohmah, Babur; Maskud, Maskud; Anam, Syamsul; Maulana, Bayu Wahyu (Abjadia : International Journal of Education, 2025)
Availability of appropriate books and in accordance with the rules of preparation of teaching materials (textbooks) will certainly help the successful implementation of the latest curriculum. Moreover, the learning process and Arabic language textbooks published by the latest Ministry of Religion have presented a Genre Based Approach. The purpose of this study was to determine the implementation of the Genre Based Approach in the Arabic language textbook material for the ninth grade students of Madrasah Tsanawiyah. This research uses a qualitative approach with the type of literature study. The qualitative data was obtained through documentation techniques. The results showed that the implementation of genre pedagogy was not perfect. There are still some patterns that have not been presented in this textbook. Among them, the discussion of the type of text, the structure of the text, and the social purpose of the text and the inappropriate placement of exercises.